Genetic polymorphisms of the NOD1,CXCL16,STAT6,TLR4, ATG16LI and IRGM Genesin Malaysia patients with crohn's disease / Ng Jin Guan - Ng, Jin Guan (2014)
Crohn’s disease (CD) is one of the major type of inflammatory bowel diseases (IBD) that affects the gastrointestinal tract. There were a lot of susceptible genes being published based on different population studies as well as meta-analysis projects. In this study, we aimed to investigate the association of some genes, NOD1, CXCL16, STAT6, TLR4, ATG16L1 and IRGM had been found with association to the disease on non- Malaysian population. Overall, 85 CD DNA samples and 250 control healthy samples were collected from University Malaya Medical Center (UMMC). DNA were extracted and analyzed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) or TaqMan assay amplification. Results obtained showed that NOD1 (PG/A=0.5179, ORG/A=1.135, 95% CIG/A=0.786 – 1.637), STAT6 (PA/G=0.531, ORA/G=0.884, 95% CIA/G=0.621 - 1.258) and IRGM variants (Prs4958847=0.154, Prs11747270=0.09359, Prs72553867=0.8844) had no association with CD. CXCL16 (PC/T=0.04819, ORC/T=1.431, 95% CIC/T=1.009 - 2.031), TLR4 (PC/T=0.007, ORC/T=0.437, 95% CIC/T=0.242 - 0.789) and ATG16L1 variant rs2241880 (PA/G=0.01462, ORA/G=0.645, 95% CIA/G =0.454 - 0.917) were found to be associated with Malaysian patients. For stratified analysis, TLR4 (P=0.0002399) and ATG16L1 rs2241880 variant (P=0.03619) were significantly associated with Malay while ATG16L1 variant 6754677 (P=6.3x10-3) was associated with Indian patients. In conclusion, CXCL16, TLR4 and ATG16L1 but not NOD1, STAT6 and IRGM were found to have strong association with CD in the Malaysian population.